PENGGUNAAN TERPAL DAN GRID BAMBU SEBAGAI ALTERNATIF PERBAIKAN TANAH TERHADAP PENURUNAN PONDASI DANGKAL PADA TANAH GAMBUT - Dewi, Ratna; Sutejo, Yulindasari; Faskal, Faskal (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2016)
Ground improvement techniques are commonly performed on peat soil is improved physically using geosynthetic materials. The often used is geotextile. In this study the use of geotextile replaced with the use of a tarpaulin and bamboo grid. They are used as reinforcement materials that is expected to be an alternative to increase the bearing capacity of peat soil which is used as the based of shallow foundation. The aim of this study is to determine the increase in the bearing capacity of variation in depth of reinforcement to the base foundation (0,25B; 0,5B; 1B) and variation in width of reinforcement (2B, 3B, 4B) to the value of bearing capacity withouth reinforcement. The research methodologies used is laboratory-testing. The data obtained from these tests were analyzed by comparing the value of bearing capacity between unreinforced soils and reinfoces soils reffered as Bearing Capacity Ratio (BCR). The results showed that the variation in the depth of the tarpaulin and bamboo on the basic foundation of the grid did not always show a rise greater carrying capacity , however, wide variations in accretion reinforcement always indicates an increase in the carrying capacity of the land. In the distance variation of reinforcement to the foundation, the maximum increase is shown at a depth of 0,5 B with a width of reinforcement for the 4B qu at 20,44 kPa. The largest value of BCR is variation in depth of reinforcement to the base foundation 0,5 B and variation in width of reinforcement 4B with a value of 3,78 and a percent increase of 277,8 %.